IMPACT OF THE LONG LASTING ISOLATED POLICY OF NORTH EAST , WITH RISE OF INSURGENCY AND ITS EFFECT ON THE ENTIRE COUNTRY AND NATIONAL SECURITY OF INDIA - Dr.Sumanta Bhattacharya; Dr. Jayanta Kumar Ray; Arup Raha; Bhavneet Kaur Sachdev (Galaxy International Interdisciplinary Research Journal, 2021)
North East area is very crucial when it comes to environment. The region because of its isolation policy from the rest of the country and lack of development because of their strategies, the armed groups and ongoing counter –insurgency in the area creates tremendous impact on the local people life . The area is full of conflict and insecurity , there also war among the ethnic groups , people fear lose of identity . However in recent years things have changed in the region with massive development happening , India and other countries are investing in the region , aiming to make it the economic hub of India and a tourist attraction place . Development in the form of Roads , highways , railways and airways have taken place. The second largest road – rail bridge has been considered in Assam , which will also influence India and Bangladesh trade creation in a positive manner .India is trying to connect more with the people and organizing meeting on a regular basis with the Chief Minister and Governors of the state . Arunachal Pradesh is experiencing regular threat from China , trans-border conflict is at a rise . However the positive impact of investment in the North-East India has cut down the violence by 90% .